Antibody–Drug Conjugates for Cancer Therapy - Umbreen Hafeez; Sagun Parakh; Hui K. Gan; Andrew M. Scott (Molecules, 2020)
Antibody–drug conjugates (ADCs) are novel drugs that exploit the specificity of a monoclonal antibody (mAb) to reach target antigens expressed on cancer cells for the delivery of a potent cytotoxic payload. ADCs provide a unique opportunity to deliver drugs to tumor cells while minimizing toxicity to normal tissue, achieving wider therapeutic windows and enhanced pharmacokinetic/pharmacodynamic properties. To date, nine ADCs have been approved by the FDA and more than 80 ADCs are under clinical development worldwide. In this paper, we provide an overview of the biology and chemistry of each component of ADC design. We briefly discuss the clinical experience with approved ADCs and the various pathways involved in ADC resistance. We conclude with perspectives about the future development of the next generations of ADCs, including the role of molecular imaging in drug development.